2020
DOI: 10.21203/rs.2.21129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The magnitude and Associated Factors of Pneumonia Among Under-Five Children in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background Currently, Pneumonia is the leading cause of morbidity and mortality among under-five children in developing countries including Ethiopia. Despite, these problems are easily preventable and treatable it contributes to more than 18% of deaths of under-five children every year in Ethiopia. Regardless of these facts, there is a paucity of information regarding the magnitude and its predictors of pneumonia in Ethiopia. Thus, assessing the pooled magnitude of pneumonia and its predictors among under-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…Our finding was in agreement with a study done in other parts of Ethiopia ( 15 , 18 ). However, the result of this study was greater than that of the study conducted by Merkeb and Fentahun(20.68%) ( 14 ) and lower than that of a study conducted in Uganda (53.7%) ( 20 ). This difference may be due to the study design (Merkeb and Fentahun conducted a systematic review and meta-analysis) and socioeconomic status variations and health service facility accessibility in the study area for the study in Uganda.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Our finding was in agreement with a study done in other parts of Ethiopia ( 15 , 18 ). However, the result of this study was greater than that of the study conducted by Merkeb and Fentahun(20.68%) ( 14 ) and lower than that of a study conducted in Uganda (53.7%) ( 20 ). This difference may be due to the study design (Merkeb and Fentahun conducted a systematic review and meta-analysis) and socioeconomic status variations and health service facility accessibility in the study area for the study in Uganda.…”
Section: Discussioncontrasting
confidence: 84%
“…This study indicated that unvaccinated under-five children were 3.5 times [AOR = 3.59, 95% CI: 1.491–8.662, p = 0.004] more vulnerable to suffering from pneumonia as compared to those children who completed their vaccination (as shown in Table 3 ). This result was supported by different studies conducted on predictors of pneumonia ( 14 , 18 , 24 ). This association could be due to the loss of strong enough immunity for causative agents.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations